Perceived psychological stress among undergraduate students: role of academic factors of a medical college of Kathmandu - Tuladhar, Jyoti Badan (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: Stress refers to a dynamic interaction between the individual and the environment, which described as external demands (physical or mental) on an individual’s physical and psychological well-being. The objective of this study was to assess the perceived psychological stress and perception of academic stress among undergraduate students.Methods: A cross-sectional, questionnaire- based survey was carried out among 853 undergraduate students (medical, dental and nursing) of Kathmandu Medical College, Kathmandu Nepal during August 2017 to July 2018. Perceived stress was assessed using Perceived Stress Scale-14 and perception of academic stress 18-item questionnaire was used to assess the academic factors of stress using self-administered technique.Result: The overall mean perceived stress score was 45.23 ±4.96, 99.6% of participants were in the group of more stressed and overall mean score of perception of academic stress was 54.68 ±9.10, and 56.3% of participants were in the group of academic stress. The correlation between perceived psychological stress and academic stress was 0.070 with P value of 0.040.Conclusion: Higher level of perceived stress and academic stress were reported by the students and there was weak significantly positive correlation between perceived psychological stress and academic stress.